PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI TERHADAP PRODUKTIFITAS KERJA DI PT. MAYORA INDAH TBK PLANT PANGKALPINANG BAGIAN PRODUKSI CANDY - Fernando, Edrean; Panjaitan, Fery; Maharani, Yunita (Jurnal Progresif Manajemen Bisnis, 2023)
The purpose of this research is to knowing the influence of communication and leadership style in partial of a work productivity in PT. Mayora Indah Tbk Plant Pangkalpinang Section Candy Production by population around 839 peoples. The sample of method in this research is doing by Proportionat Random Sampling Technique. The technique can do if the population has member or element are not homogeny and stratified and proportionately. Methodology of this research is quantitative method. This research use the quantitative data from questionnaire of SPSS 21 Program for Windows. This research use method of analysis data Multiple Linear Regression that has qualified validity, reliability, normaly test, multicolonierity test, heteroscedasticity test, autocorrelation test, coefficient of determination, hypothesis testing with test-F and test-t. The results of stastical calculasions partially (Test-t) analysis shows that leadership style variables have a positive and significant influences for a work productivity with t-count >t-table or 8,819> 1,988 with a significant level 0,00. And for communication variable have positive and significant influences for a work productivity with result t-count>t-table or 4.590>0,1988 with significant level 0,00. The simultaneously of communication and leadership style have positive and significant influences for a work productivity with F-count>F table or 168.960>3.10 with 0,000 significant level with R square result around 0,792 or 79,2%.